Faktor-faktor yang Mempengaruhi Inflasi Di Indonesia: Model Demand Pull Inflation - Maggi, Rio; Saraswati, Birgitta Dian (Jurnal Ekonomi Kuantitatif Terapan; 2013: Vol. 6, No. 2, Agustus 2013 (pp. 71-143))
This study’s aim is to analyze the effects of factors like money supplies, interbank interest rate (PUAB), crude oil price and season change factor (dummy) to the inflation rate in Indonesia. Using time series secondary monthly data during period 2001.1 – 2011.12, which is collected from several numbers of literatures and also used co-integration equation with error correction model (ECM) as researching tool, this study will analyze the relationship between independent variabel and dependent variabel in both long-run and short-run period. The estimation result of co-integration equation showed that money supplies, interbank interest rate (PUAB), and crude oil price significantly affected the Indonesian inflation rate in the long-run period, but season change factor (dummy) didn’t. While the Error Corecction Model (ECM) which is considered valid because it’s significant error correction term (ECT) showed that only interbank interest rate (PUAB) which is significantly effected the inflation rate of Indonesia in short-term period, while money supplies, crude oil price and season change factor (dummy) didn’t.
Keywords: inflation , money supplies , interbank interest rate (PUAB) , crude oil price , season change factor , co-integration , error correction model